Diminishing Returns of Leadership Behaviors on Leadership Emergence. (December 2019) - Mitchell, Tyree David; Hu, Jasmine; Johnson, Lars
A large body of evidence has concluded that there are positive linear relationships between leadership behaviors and leadership emergence. Drawing on insights from the leadership and teams research, we hypothesized that above certain levels of task-oriented and relationship-oriented behaviors, such behaviors will have diminishing returns for leadership emergence. Hypotheses were tested using a sample of 105 leaderless teams within an assessment center setting. Our results indicate that team members' behaviors have linear and non-linear relations with leadership emergence. We discovered that the association between relationship-oriented behaviors and leadership emergence in self-managed teams is curvilinear, whereas the association between task-oriented behaviors and leadership emergence is linear but not curvilinear. Overall, the relationships between member behaviors and leadership emergence are more complex than the independent, positive linear relationships observed throughout the literature.